Designing interactions for music and sound - Filimowicz, Michael (Sound design series, 2022)
"Designing Interactions for Music and Sound presents multidisciplinary research and case studies in electronic music production, dance-composer collaboration, AI tools for live performance, multimedia works, installations in public spaces, locative media, AR/VR//MR/XR and health. As the follow-on volume to Foundations in Sound Design for Interactive Media, the authors cover key practices, technologies and concepts such as: classifications, design guidelines and taxonomies of programs, interfaces, sensors, spatialization and other means for enhancing musical expressivity; controllerism-the techniques of non-musician performers of electronic music who utilize MIDI, OSC and wireless technologies to manipulate sound in real time; artificial intelligence tools used in live club music, soundscape poetics and research creation based on audio walks, environmental attunement and embodied listening; new sound design techniques for VR/AR/MR/XR that express virtual human motion; and the use of interactive sound in health contexts, such as designing sonic interfaces for users with dementia. Collectively the chapters illustrate the robustness and variety of contemporary interactive sound design research, creativity and its many applied contexts for students, teachers, researchers and practitioners"--